2022
DOI: 10.1007/s00531-022-02190-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and structure of karstification of the Dong Van Karst Plateau UNESCO Global Geopark, North Vietnam based on cave survey data

Abstract: This paper presents a quantitative study of the relationship between the cave system and the tectonic and karst evolution of the Dong Van Karst Plateau based on analysis and statistics of geometric parameters and orientation of cave passages. The region is located in northern Vietnam and belongs to the extended part of the South China karst belt (Yunnan karst plateau), which is composed mainly of carbonate rocks. Cave classification based on cave conduits geometric parameters shows that caves developed mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Individual research on the hydrogeochemical progress of coastal aquifers and the factors restraining them have been managed. In the last five years, the research of [18]; [19]; [20]; [21] and [22] have been studied in different areas worldwide. These studies have shown that the groundwater constituents and quality are affected by native factors (such as water-rock interactions, climate variation, geological settings, etc.)…”
Section: Hydrogeochemistry Methodmentioning
confidence: 99%
“…Individual research on the hydrogeochemical progress of coastal aquifers and the factors restraining them have been managed. In the last five years, the research of [18]; [19]; [20]; [21] and [22] have been studied in different areas worldwide. These studies have shown that the groundwater constituents and quality are affected by native factors (such as water-rock interactions, climate variation, geological settings, etc.)…”
Section: Hydrogeochemistry Methodmentioning
confidence: 99%